The Promotional Effect of Health Education on the Medical Service Utilization of Migrants: Evidence From China - Tian, Yihao; Luo, Tao; Chen, Yuxiao (Frontiers in Public Health, 2022)
There were 376 million migrants in China by 2020, who made significant contributions to urban development. However, they used limited medical services and had lower self-reported health status than inflow city residents. Based on this, this study uses the cross-sectional data of the 2017 China Migrants Dynamic Survey (CMDS) to construct a multiple linear regression model to empirically study the role of health education in improving medical services utilization for migrants. It finds that compared to migrants without health education, the probability of the medical service utilization for migrants with health education has increased significantly, and counseling is more effective than other methods for health education. This promotion effect of health education has been established after a series of robustness tests. Furthermore, this study finds that the closer the migrants are to medical service resources, the greater the effect of health education on medical services utilization for migrants. The heterogeneity test shows that the effect of health education on medical services utilization for migrants is greater among the non-elderly and those with lower education levels. From the perspective of health education, the findings in this study provide empirical evidence to support the government in formulating policies to improve the utilization of medical services for migrants and reduce health inequality.